Digital Education Governance: Implementation of Information Technology-Based Supervision - Joulanda A.M. Rawis; Meiny Conny Sumilat (PT. NALURI EDUKASI PRESS, 2024)
The digital transformation of educational supervision presents both opportunities and challenges in modern education governance. This study examines how information technology reshapes traditional supervision mechanisms through a comprehensive literature analysis. The research identifies three significant findings. First, supervision systems are undergoing a fundamental transformation from conventional methods to technology-driven approaches. This shift enables real-time monitoring, data-driven decision-making, and enhanced feedback mechanisms. Digital platforms facilitate more efficient communication between supervisors and educators while streamlining administrative processes. Second, the evolution of supervisory roles demands new digital competencies from education supervisors. These include proficiency in digital tools, data analysis capabilities, and understanding of online pedagogical practices. The complexity of these requirements necessitates systematic professional development and training programs. Third, successful implementation requires a robust digital governance architecture. This framework must integrate various technological components while ensuring data security, accessibility, and interoperability. The system should support adaptive supervision practices that respond to evolving educational needs and technological advances. The study concludes with practical recommendations for education stakeholders. Investment in continuous professional development programs is essential to build and maintain digital competencies among supervisors. Technical infrastructure must be redesigned to support comprehensive digital supervision systems. Additionally, implementing a holistic approach that considers both technological and human factors is crucial for successful digital transformation in educational supervision.